The Significance of Multimodal Discourse Framework on Joker Poster of BPJS Kesehatan - Pasopati, Rommel Utungga; Saputro, Dimas Eko; Sarmi, Ni Nyoman; Arditha, Lisma Ayu; Rafiuddin, Rizal (Universitas Brawijaya, 2026)
This article exposes the significances of multimodal discourse analysis alongside with its analysis on BPJS Kesehatan’s poster regarding Joker as a DC character. In its finding, this paper finds that a poster distinctively contains various discourses within including the colors, the words, the messages, and the image as well. A poster does not stand alone or merely being seen in its purpose. Supported by Gunther Kress and Theo van Leeuwen, multimodal discourses reflect structured meanings of representations between the image and the common reality. The image of Joker is detrimental to those who suffer mental disorder. The poster may inform the covering of social health coverage, but it also shows keeps the sufferers to be undermined by society. The figure of Joker also tends to shape perceptions that mental disorder sufferers could always be as violent as that DC character. Through Multimodal Discourse Analysis (MDA) analysis, the poster uses pictures, words, and symbols to send a message, but these can be understood in many ways by the audience. The study shows that poster does not only give information but also create new meanings through social and cultural views. The use of Joker gives a risk of creating wrong ideas about people with mental health problems, making them look dangerous. This shows the need for more care and awareness in public health communication. In conclusion, the poster and the image of Joker exposes multimodal discourses in which the reality of normal people is contrasted with the sufferers of mental disorders.